Legal Foundations and Inequities in Indonesian Autonomy: Landasan Hukum dan Ketidakadilan dalam Otonomi Indonesia - Umam, Abd.; Yusuf, Dwi Savedo; Rato, Dominikus; Setyawan, Fendi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the effectiveness of Indonesia's regional autonomy laws—Law Number 22 of 1999, Law Number 32 of 2004, Law Number 23 of 2014, and Law Number 5 of 2014—highlighting the challenges of inter-regional inequality, conflicts of interest, and resource limitations. Employing qualitative analysis of legal documents and secondary data, the research identifies critical gaps in the legislation that hinder equitable development across regions. It proposes legal reforms to strengthen the governance system, aiming to enhance fairness and effectiveness in regional autonomy, thereby ensuring a more balanced national development. Highlights: Legal Gaps: Current laws insufficiently address inter-regional inequalities and conflicts. Reform Necessity: Legal reforms are crucial for effective resource distribution and conflict management. National Impact: Improved laws can enhance national unity and regional governance. Keywords: Regional Autonomy, Legal Analysis, Inequality, Conflict Resolution, Policy Reform